West African Economic and Monetary Union (WAEMU) : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper presents stylized facts on the quantitative and qualitative infrastructure gap in the West African Economic and Monetary Union (WAEMU), estimates the efficiency of public investment, and recommends how to improve it. The WAEMU countries face an important common challenge of creating sufficient fiscal space to finance ambitious growth, development, and poverty-reduction programs in individual countries. This paper also provides comparative evidence of the situation of WAEMU in several areas of financial development relative to groups of benchmark countries. The state of inclusion in the WAEMU along three dimensions-poverty, income inequality, and gender inequality-is also examined in this paper.